Rekonsiliasi Kelekatan Antar Siswa Kelas Rendah Melalui Sikap Demokratis Pada SDN Bulusari 3 Kabupaten Kediri - Fahri Ana Latifah; Novi Nitya Santi; Frans Aditia Wiguna (Jayapangus Press, 2022)
This study aims to determine the reconciliation between democratic aspects and aspects of attachment and how relevant it is. The low emotional closeness between students causes students to become uncomfortable in socializing, fighting with each other, making friends in groups, and bullying. This study uses a qualitative method with a descriptive approach. The data was obtained in the low class, namely class III at SDN Bulusari 3 Kediri. Based on the results of the research that reconciliation of attachments between low grade students can arise through aspects of attachment, namely trust, communication, and alienation. While the democratic aspect is freedom of expression, group freedom, freedom to participate, equality between friends, trust, and cooperation. Then for the impact of the reconciliation of attachments that between students can give a good response to each other by restoring or increasing the relationship of attachment through democratic aspects in the learning process. For this reason, the reconciliation aspect with the democratic aspect is very relevant or interconnected if it is implemented in the learning process.